Flow generated by a thermal plume in a cooled-ceiling system - Thomas, Luis Pablo (2011)
The transient and steady states of the flow generated by a heat source inside a closed room provided with a cooled-ceiling system at constant temperature are experimentally studied. During the transient regime the plume generated by the source interacts with the ambient fluid and, after it reaches the top contour, spreads under the latter giving place to the formation of a horizontal thermal front that eventually descends affecting the whole room. It is found that the formation and velocity of the descending front are determined by the filling-box model in an insulated space but with a smaller temperature difference between both sides of the front. The steady state is established when the heat supplied by the source is completely absorbed by the ceiling allowing a convective process to take place characterized by a turbulent flow in the major part of the room and by a thermal boundary layer developed below the ceiling, where vortexes and little plumes form, the detection of which is allowed by the application of synthetic schlieren technique. Analogies with the results obtained in the classical Rayleigh-Benard experiments allow an insight of the mechanisms of heat transfer in order to improve the indoor comfort in buildings under similar conditions to those discussed here.